Revision of the genus Pozziella (Porifera: Poecilosclerida) with description ofthree new species from the eastern Pacific - Díaz-Agras, Guillermo (Zootaxa, 2008)
To date, the poecilosclerid sponge genus Pozziella Topsent, 1896 was represented by two species: Pozziella clavisepta Topsent, 1896 and Pozziella aperta (Topsent, 1920), which are presently redescribed. During the campaign SO 144-3a of the project PAGANINI in the Pacific Ocean between the Galapagos Archipelago and Central America, three new species were recovered and are described here: Pozziella cerilla sp. nov., Pozziella neuhausi sp. nov. and Pozziella lueteri sp. nov. The present study led to a revision of the genus and an attempt to resolve the relationships between the species, based on the likeness of spicule complements and biometric characters. A similarity analysis revealed that Atlantic and Pacific species clustered separately. In addition, a key to all species of the genus based on spicular characters is provided.